Missing the Forest for the Trees - Potter, Jordan (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
This response expands on Wyzynski’s focus of the importance of fostering elementary ethics deliberation and education within hospitals. In particular, it highlights that most of the clinical ethicist’s work revolves around basic, fundamental ethical dilemmas, as well as the importance of ethics education being within the clinical ethicist’s scope of practice and responsibility.